Textual Configuration Analysis: a lesson by L. S. Vigotski - Amabriane da Silva Oliveira Shimite; Fabiana Oliveira Koga (Universidade Federal do Rio Grande do Sul, 2020)
The analysis of the text/class The student's thinking was carried out a reflecting on the synthesis of the concepts that constitute the Historical-Cultural Theory, with emphasis on the development of human consciousness. The method for such action was the documentary analysis and the interpretation procedure employed was the textual configuration analysis. Aspects of the historical context and translation were analyzed, as well as the synthesis of concepts presented by Vigotski for teachers in training. The attempt to clarify, exemplify, contextualize and demonstrate to teachers the need to reflect on the concepts of the Historical-Cultural Theory, in pedagogical practice, explored the conceptual thinking in the process of child development.